(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article examines the role of human anatomy in the era of telemedicine and digital diagnostics. It explores how advances in information technologies, including telemedicine platforms, digital imaging systems, and remote diagnostic tools, have transformed the study and clinical application of anatomical knowledge. Particular attention is paid to the integration of anatomical data with medical imaging technologies such as computed tomography, magnetic resonance imaging, and ultrasound in remote healthcare settings. The article highlights the importance of anatomical competence in ensuring accurate digital diagnostics, supporting clinical decision-making, and improving patient outcomes. The study is intended for medical students and healthcare professionals adapting to technology-driven medical practice.